Implementation of the Merdeka Curriculum in a Pioneer Elementary School: A Qualitative Study of Planning, Pedagogy, and Assessment Practices - Syamsidar, Syamsidar; Rahmah, Nur; Muslim AR., Muslim AR.; Rizal, Rizal; Wilade, Surahman (Papanda Publisher, 2025)
This study examines the implementation of the Merdeka Curriculum at SD Negeri 6 Palu, one of the pioneer schools in Central Sulawesi. Using a qualitative descriptive approach, the research involved three teachers representing Phase A (grades 1-2), Phase B (grades 3-4), and Phase C (grades 5-6). Data were collected through classroom observations during three learning sessions, semi-structured interviews conducted over three days (60 minutes each), and document analysis of teaching modules, learning objectives flow, and learning outcomes. The findings reveal that curriculum implementation has been carried out effectively across three stages. In the planning stage, teachers systematically analyzed government-provided learning outcomes, developed learning objectives flow, and created comprehensive teaching modules aligned with curriculum requirements. During implementation, teachers employed student-centered pedagogical approaches including differentiated instruction, varied teaching methods, and contextual learning appropriate to students' developmental levels. In the assessment stage, teachers utilized diagnostic, formative, and summative methods through multiple instruments including oral tests, written examinations, and performance-based assessments. The study demonstrates that intensive professional development and institutional commitment enable successful curriculum implementation. However, variations in implementation sophistication suggest the need for sustained professional learning communities to support continuous pedagogical refinement. Future research should examine implementation across diverse school contexts and include student learning outcomes and stakeholder perspectives.